2016
DOI: 10.3844/ajassp.2016.609.617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Pretreatment on BMP of Decanter Cake from Palm Oil Mill Factory

Abstract: Anaerobic digestion is an effective method for treating decanter cake in the biogas production. Decanter cake usage is limited by its slow fiber degradation for anaerobic digestion process. The aim of this study is to study the possibility of using microwave pretreatment to enhance decanter cake digestibility. The power and heating time are the parameters that influence the biogas production and methane yield. The Biochemical Methane Potential (BMP) tests are used in this study to find the optimization setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Percentage of total volatile solid of food waste and palm oil waste were not measured in this experiment but in studies carried out by Lalander et al . (2019) and Kaosol and Rungarunanotai (2016) , food waste and palm oil decanter cake had a total volatile solid value of 89.8 ± 4.0% and 87.3 ± 0.4% respectively. BSF larvae fed on fish waste had the fastest development time (11 days), but an overall lowest pre-pupae weight.…”
Section: Discussionmentioning
confidence: 96%
“…Percentage of total volatile solid of food waste and palm oil waste were not measured in this experiment but in studies carried out by Lalander et al . (2019) and Kaosol and Rungarunanotai (2016) , food waste and palm oil decanter cake had a total volatile solid value of 89.8 ± 4.0% and 87.3 ± 0.4% respectively. BSF larvae fed on fish waste had the fastest development time (11 days), but an overall lowest pre-pupae weight.…”
Section: Discussionmentioning
confidence: 96%
“…The pretreatment of DC was done in different methods. Based on the research by Thaniya Kaosol (30), the DC that has gone through oven pretreatment produced a higher methane yield compared to unpretreated DC by around 25%. This was further supported by Chonticha Rongwang's research (32) as seen in table 2.4.2, showed that the use of ozone pretreatment increased the methane yield by around 24 -52 % and thermal pretreatment increased by 3% -9% compared to untreated DC.…”
Section: Decanter Cake (Dc)mentioning
confidence: 99%